El surgimiento del enclave bananero en el Pacífico Sur - Cerdas Albertazzi, Ana Luisa (1993)
Settlement of South Pacific region of Costa Rica has begun before the establishment of the banana enclave. This process was interrupted by the presence of UFCO, given its monopolistic nature, but especially due to the political concessions granted to the company by the Costa Rica state.